Synthesis of 2-mercaptobenzothiazole, substituted metal phthalocyanine complex, and investigation of electrochemical and thermal properties - Saydam, Sinan; Hamad, Othman Abdulrahman (Sage Publications Ltd, 2026)
Phthalocyanines (Pc) complexes are versatile, highly conjugated planar macrocycles known for robust thermal stability and tunable electronic properties, making them valuable in catalysis, sensing, and energy applications. Herein, we report the synthesis of novel chromium(II) and iron(II) phthalocyanines bearing peripheral 2-mercaptobenzothiazole (2-MBT) substituents. The 2-MBT groups introduce sulfur- and nitrogen-containing aromatic thiolate functionality to the macrocycle periphery, aimed at extending pi-conjugation and modulating the electronic structure of the phthalocyanine core. This functionalization strategy is expected to tailor the optical and redox characteristics of the complexes. Structural characterization via elemental analysis, Fourier-transform infrared (FT-IR), ultraviolet-visible (UV-Vis), and 1HNMR spectroscopy confirmed successful formation of the macrocyclic complexes. Notably, the disappearance of the phthalonitrile C equivalent to N stretching band in FT-IR indicated complete cyclotetramerization into the MPc framework. The UV-Vis spectra exhibited characteristic Q-bands at 683 nm and B-bands at 300-350 nm, consistent with pi-pi* transitions of the conjugated ring. Thermogravimetric analysis revealed that both complexes remain highly thermally stable up to 250 degrees C before undergoing stepwise exothermic decomposition. Electrochemical studies cyclic voltammetry and square-wave voltammetry in dimethylformamide, showed multiple quasi-reversible redox processes associated with both the phthalocyanine pi-system and the central metal ions. These findings demonstrate that the 2-MBT-functionalized phthalocyanines are thermally robust and redox-active, with promising potential for electrocatalysis and catalysis.
Keywords: metal phthalocyanine; 2-mercaptobenzothiazole; 4-NPN; thermal analysis; electrochemistry